IMPLEMENTASI PENATAAN DESA TERDAMPAK LUMPUR LAPINDO DI DESA KETAPANG KECAMATAN TANGGULANGIN - Sifak Duwi Kistanti; Lailul Mursyidah (Halu Oleo University, 2024)
This study examines the implementation of village planning due to Lapindo mud in Ketapang Village. The 2006 Lapindo mud has caused severe damage, one of which is Ketapang Village, Tanggulangin District, causing administrative services to be unable to run. This study aims to identify the implementation of village planning in Ketapang Village, Tanggulangin District. The research method is based on qualitative description with observation, interviews, and documentation. The results of the study show that the implementation of village planning in Ketapang Village, Tanggulangin District is running optimally including communication with the local government, village government, and community so that it produces mutually agreed decisions, adequate human resources in carrying out administrative services and financial resources that support the merger of villages, and support from stakeholders so that activities and administrative services in Ketapang Village, Tanggulangin District can run like villages in general after being affected by Lapindo mud.